Challenges in immunodiagnostic tests for leprosy. (May 2013) - Geluk, Annemieke
<x xml:space="preserve">Abstract</x> Introduction: Despite the effectiveness of multidrug therapy, leprosy still represents a significant global health problem: transmission of Mycobacterium leprae (M. leprae) is not sufficiently reduced as witnessed by unwavering new case rates in leprosy-endemic countries. Early detection of M. leprae infection (before clinical manifestations occur) is vital to reduction of transmission. Current diagnosis relies on detection of clinical signs since there are no tests available to detect asymptomatic M. leprae infection or predict progression to leprosy. Areas covered: Identification of risk factors (immunological or genetic biomarkers) for disease development and/or onset of leprosy reactions is imperative for efficient diagnosis. Tests simultaneously detecting biomarkers specific for cellular and humoral immunity are well suited for diagnosis of different clinical outcomes of leprosy. This review describes the challenges of discovery of biomarkers for M. leprae infection and their implementation in field-friendly tests. Expert opinion: In view of the complicated nature of M. leprae infections, it is essential to invest in longitudinal studies allowing intra-individual comparison of immune and genetic biomarkers in various leprosy-endemic areas. Furthermore, the effect of co-infections on biomarker profiles should also be taken into account. Diagnostic tests based on such biomarkers can contribute significantly to early detection of leprosy (reactions) thus helping reduce nerve damage.